Propuesta de automatización del sistema de izaje para el proceso de extracción de material aurífero en la empresa minera Labor Minera Manuel Castillo. - Blacio Matamoros, Kevin Gabriel (2021)
Automation is a benchmark for development and competitiveness, increasing productivity and production capacity, with this approach the automation proposal was made at the Labor Minera Manuel Castillo company to take advantage of the maximum capacity for extraction of gold material in the lifting process. This current situation is carried out with a hoist generating excessive and monotonous load for the workers with unproductive times, unnecessary and high costs. In this sense, it is proposed to improve the LIFTING process, which represents the greatest obstacle in the extraction of gold-bearing material. With the study of the characteristics of the current process with the methods and measurement of the work, raising the processes with evaluation and control tools, with this, the automation proposal was made, which is an automatic lifting system, exposing its technical and engineering aspects as design. , functionality, power calculations, speed of Positioning with all these aspects, consequently, the functionality of the lifting system is simulated with the SolidWorks software and the simulation of the automated lifting process in the ProModel software comparing the results with the current hoist system in the lifting. Finally, the costs of the automated proposal of Izaje, its viability for its implementation and denoting its positive results in all aspects are evaluated as extractive capacity that is currently 96 tons and with the automation proposal is 123.8 tons per semester producing for the mine an increase in Big Bag from 20 tons to 25.78 tons per semester that can be sold increasing its purchasing productivity of $ 18,084,434 dollars per year, reducing lifting time from 9 hours to 5.63 hours with fewer human resources minimizing costs, this is achieved with an investment of $ 28'024.68 that has a return in 11.48 months, being viable for the management and interested parties of the mine.